Transições paradigmáticas contemporâneas na universidade: um estudo sobre a proposta da integralidade - Calgaro Neto, Silvio (2011)
As the title of the dissertation presents, this is a study on the contemporary paradigmatic transitions at the University. However, on the elaboration were made some assumptions and beliefs concerning due process in the composition of the western societies institutions, which was previously considered some existents unbabelization processes , this term being used to represent the increasing accessibility of western societies on their institutions. As an example, we tried to work with three representative fields of this process: political, cultural and environmental fields. However, the empirical research have been leaned to the observation of the cultural field, which presented facts and ideas in the context of the Universidad de la República, where are coming up the implementation of the integrality proposal . This proposal shows the direction for the development of other university institutional model, dedicated, mainly, to interdisciplinary, integration between the general function of the university - Education, Research and Extension -, for horizontal dialogue with popular cultures, to evidence the social commitment of this institution, etc. In this sense, we tried to understand societies as transitional forms and continuously changing. These perspectives were subsidized to some theoretical supports, they are; The Structuration Theory, by Anthony Giddens, which integrates structure and action to read the societies constitution, revealing the potential of the critical reflection process for social transformation; Chaos Theory, inserting unsolved problems showed by Giddens Theory, as the unconscious and unintended action consequences; and, moreover, was tried to reflect about the implications of modern design in societies, and in the development of the academic spaces of formation and transformation, in this case, using the contributions of Jack Mezirow, who brings the Transformative Learning Theory. As will be showed reading this dissertation, interacts here, especially with Critical Theory, as an indicator for social transformation processes; Chaos Theory, as an indicator of complexity and chaos presence on the social construction of reality; Complexity Science, as an indicator of seeking to paradigmatic overcome and the emergence of other western cultural dialogue, and; Deep Ecology, as an indicator of the elements in the quest for environmental sustainability. The empirical research, organized with participants of activities conducted within the framework of the integrality proposal , aimed to find indicators for the observation of unbabelization process , and tried to observe the potential skills of pedagogical proposes to promote critical reflection on its members, looking to the use of different methodological tools and their participatory action research approaches, realizing that like the institutional idealization of UDELAR to conduct the formative spaces. Briefly, was observed the guidelines proposals and idealizations for the academic formation, relative to agricultural sciences, understanding them as susceptive to multiple influences. Finally, there was a discussion about the difficulties presented to the expected transitions in the three fields studied, in order to support the unbabelization process , however, the progress of the indicated process claims to the need of promote various dialogues, about politics, in public management, about culture, in the management and production of knowledge, about environment, within the quest for sustainability. In this context, was understood that these dialogues are not comfortable to the western societies, emerging a big question: will it be possible, to the western societies, overcome the comfort paradox ?